James Coleman. - Städtische Galerie im Lenbachhaus; Kunstbau München (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
In a detailed essay, the film theorist Kaja Silverman discusses the four works Background (1991-94), Lapsus Exposure (1992-94), Initials (1993/94) and Photograph (1998/99)
The Irish-born artist James Coleman became known throughout the eighties and nineties with audiovisual works that are extraordinarily precise, both with respect to their pictorial and their literary qualities. Artists such as Douglas Gordon, Stan Douglas or Steve McQueen profess to have been greatly influenced by them. His videos, films and theatre projects and especially his large-scale slide projections are quite exceptional : Coleman presents tightly orchestrated social situations in colourful multiple fade-over stills accompanied by spoken text with a highly differentiated sound track. Although the pictures shown are reminiscent of scenes from daily life, film or literature, their narrative structure remains metaphorical. questions of perception are supplied with psychological, cultural and historic dimensions.
bibliog. p; 174-175
ind. tent., gr. tent. p. 173-174
Duits
Engels
James Coleman, Städtische Galerie im Lenbachhaus / Kunstbau München, 20. April - 21. Juli 2002
boek
Keywords: Coleman, James